Phase Equilibria of a Mixed Alkali Soap/ Carboxylic Acid/Water System - Suhaimi, Hamdan; Kassim, Anuar; Che Rose, Laili (Universiti Putra Malaysia Press, 1993)
A preliminary investigation was carried out on the phase equilibria in the three component systems, water/sodium caprylate/octanoic acid, water/sodium caprylate and sodium dodecyl sulphate (l:1) / octanoic acid at 30°C. The phases were separated by repeated centrifugation. The birefringence was observed under cross-polarisers and their consistency, texture and optical pattern were examined under the polarizing microscope. On the basis of the results obtained, a phase diagram was drawn that includes two phases of isotropic solution and two mesophases. Results also showed a decreased amount of octanoic acid utilized in obtaining the lamellar liquid crystal phase. The critical micelle concentration was also reduced for the mixed surfactant system